BIOLOGICAL THERAPY AND INFECTIONS IN PATIENTS WITH RHEUMATOID ARTHRITIS: RELEVANCE AND PROSPECTS - B. S. Belov (Научно-практическая ревматология, 2014)
The past decades are marked by the obvious progress in rheumatology, which is related to the practical introduction of biological agents. At the same time the use of these drugs is associated with the increasing risk of infections of different nature and locations, including opportunistic ones (invasive mycoses, Pneumocystis pneumonia, etc.), and with the greater risk of reactivation of latent infection, primary with that of tuberculosis. Beyond that point, there are cases of severe infections (pneumonia, sepsis, bacterial arthritis, skin and soft tissue lesions, etc.), including those with a fatal outcome. This review analyzes mainly the past 3-year literature data on the rate and location of infections treated with biologics, which have been obtained in the placebo-controlled and direct comparative studies of patients with rheuma- toid arthritis. It characterizes the importance of different infections (tuberculosis, pneumonia, chronic viral hepati- tides, herpesvirus infections, etc.) for treatment policy in the above patients. This underlines the need for wider immu- nization with different vaccines (chiefly against pneumococcus and influenza) in patients with autoimmune inflam- matory rheumatic diseases.